2015
DOI: 10.1007/s00276-015-1491-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant anatomical parameters of the replaced right hepatic artery (RRHA)

Abstract: PurposeVascular anatomy of the liver is subjected to many variations. The most common hepatic artery (HA) replacement is the right hepatic artery (RRHA). Variations of the HA are particularly important consideration when choosing the best surgical procedure or if radiological abdominal intervention is required. In this study, we evaluated the anatomical details of the RRHA origin.MethodsRetrospective investigation of clinical data from 1569 patients who underwent an abdominal MDCT was performed. The anatomy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Another study by Yang et al demonstrated similar results with MDCT being less sensitive for detecting celiac artery stenosis [ 31 ]. Whereas Staskiewicz et al showed that detection and evaluation of vascular anomalies does not necessarily require angiography-CT, rather a MDCT is sufficient to provide the knowledge of the HA abnormalities [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Yang et al demonstrated similar results with MDCT being less sensitive for detecting celiac artery stenosis [ 31 ]. Whereas Staskiewicz et al showed that detection and evaluation of vascular anomalies does not necessarily require angiography-CT, rather a MDCT is sufficient to provide the knowledge of the HA abnormalities [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 B) . The replaced RHA, arising from SMA, was one of the most variations of the hepatic artery found in 10.1-13.2% of cases [14] , [15] , [16] .…”
Section: Discussionmentioning
confidence: 97%
“…Vascular injury may occur during pancreatoduodenectomy, cholecystectomy and pancreatectomy. The evaluation of the local anatomical details should precede abdominal surgeries 12 . Every surgeon or interventional physician should always consider the possible existence of aberrant hepatic arteries.…”
Section: Discussionmentioning
confidence: 99%